Recovering from the Global Financial Crisis - Ojo, Marianne (Business Expert Press, 2013)
Ebook from IG Library ; Why are some global financial crises more difficult to recover from and overcome than others? What steps are necessary in ensuring that financial stability and recovery is facilitated? And what kind of environment has the previous financial environment evolved to and what kind of financial products have contributed to greater vulnerability in the triggering of systemic risks? These are among some of the questions that this book addresses. In highlighting the role and importance of various actors in post-crises reforms as well as the huge impact of certain factors and products that are contributing in exacerbating the magnitude and speed of transmission of financial contagion, this book provides an insight into why global financial crises have become more complicated to address than was previously the case. Within this book, the author doesn't merely identify and highlight the general root causes of global financial crises and the current issues, but gives each chapter recommendations and measures that contribute to the magnitude and severity of global financial crises.